DYNAMIC COMPOSITION IN THE FILM THOR: LOVE AND THUNDER ON DISNEY+ HOTSTAR PLATFORM." - Martinus Eko Prasetyo (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2024)
The popularity of Marvel Studio films in Indonesia has been quite popular since the last ten years. Many films produced by Marvel Studio have received the attention of the public, one of the most recent is a film entitled Thor: Love and Thunder which is currently showing on the Disney+ Hotstar platform as one of the family's favorite films which is quite visually appealing. Based on the analysis conducted by the author of two previous studies regarding the visual composition of moving images in a Netflix film and the visual composition of a photographic still image, how to take pictures on a camera is important and the authors try to prove this through this research. By using a qualitative descriptive research method, the author dissects the application of dynamic composition in the shooting of the film Thor: Love and Thunder which is analyzed from several important scenes that occur at the beginning of the film, in the middle of the film, and at the end of the film. This research shows the importance of taking dynamic composition from the start in camera shooting of the latest 2022 Marvel film production because it has a direct effect on conveying messages to the audience.